Interconnected sub-networks of the macaque monkey gustatory connectome - Hartig, Renée; Karimi, Ali; Evrard, Henry C. (Frontiers in Neuroscience, 2023)
Macroscopic taste processing connectivity was investigated using functional magnetic resonance imaging during the presentation of sour, salty and sweet tastants in anesthetized macaque monkeys. This examination of taste processing affords the opportunity to study the interactions between sensory regions, central integrators, and effector targets. Here, 58 brain regions associated with gustatory processing in primates were aggregated, collectively forming the gustatory connectome. Correlations between regional regression coefficients (β-series) obtained during taste stimuli were used to reveal functional connectivity. This connectivity was then evaluated by assessing its laterality, modularity and centrality. Our results indicate significant correlations between same region pairs across hemispheres in a bilaterally interconnected scheme for taste processing throughout the gustatory connectome. Using unbiased community detection, three bilateral sub-networks were detected within the graph of the connectome, revealing clustering of 16 medial cortical structures, 24 lateral structures and 18 subcortical structures. Across the three sub-networks, a similar pattern was observed in the differential processing of taste qualities. In all cases, the amplitude of the response was greatest for sweet, but the network connectivity was strongest for sour and salty tastants. The importance of each region in taste processing was computed using node centrality measures within the connectome graph, showing centrality to be correlated across hemispheres and, to a smaller extent, region volume. Connectome hubs exhibited varying degrees of centrality with a prominent leftward laterality in insular cortex centrality. Taken together, these criteria illustrate quantifiable characteristics of the macaque monkey gustatory connectome and its organization as a tri-modular network, which may reflect the general medial-lateral-subcortical organization of salience and interoception processing networks.